Basic Statistics for Farm Data Processing at PT. Kembang Joyo Sriwijaya - Nurjannah, Nurjannah; Solimun, Solimun; Amaliana, Luthfatul; Mudjiono, Mudjiono (Journal of Innovation and Applied Technology, 2025)
Basic statistical analysis plays an important role in data processing in the farm industry including production, animal health and feed efficiency. PT Kembang Joyo, a bee and sheep farming company, needs to use statistical analysis to increase productivity and maintain product quality. The “Basic Statistics Training Activity in Farm Data Processing” at PT Kembang Joyo Sriwijaya includes material on data processing and analysis methods, including basic concepts of data analysis, descriptive statistics and inferential statistics, and practice in using MS Excel to process data using pivot table functions and data analysis add-ons. The evaluation of this community service activity is carried out on two aspects, the understanding of the learning materials and the participant satisfaction. The pre-post test analysis show that in general, the participants' understanding of the learning material increased significantly after the training. The satisfaction index also shows "very good" results with a service quality of "A".